Ultraviolet-curable optically clear resins using novel fluorinated imide-modified urethane acrylates. (December 2022) - Ha, Yu-Mi; Cho, Eunbee; Lim, Hyun Tae; Won, Jong Chan; Kim, Yun Ho; Kim, Yong Seok; Kim, Jinsoo
Abstract: Homologs of novel fluorinated aromatic imide-modified urethane acrylate oligomers (FI-UAs) with different flexible methylene chain lengths were successfully synthesized using 4, 4-(hexafluoroisopropylidene)diphthalic dianhydride (6FDA)-based diimide diols (FI-OHs), isophorone diisocyanate (IPDI), and 2-hydroxyethyl methacrylate (HEMA). Ultraviolet (UV)-curable optically clear resins (OCRs) were prepared using these oligomers, and the UV-curing behavior of these resins was studied by monitoring the CC bond conversion and gel fraction while varying the UV dose. The thermal (glass transition temperature and thermal stability), optical (transmittance, yellowness, and haze), and adhesion properties of the cured films were investigated. The cured films of the resins exhibited improved thermal and optical properties, except for haze, which could be primarily due to the presence of fluorinated aromatic imide moieties in the oligomer. Furthermore, higher adhesion and improved haze were observed with increasing methylene chain length of FI-UA oligomers. Graphical Abstract: UV-curable OCR materials with fluorinated aromatic imide-modified urethane acrylates. ga1 Highlights: Novel fluorinated aromatic imide-modified urethane acrylates (FI-UAs) were synthesized by using 6FDA-based diimide-diols. UV-curable optically clear resins were prepared by combining FI-UAs, (IBOA), and Irgacure 1173. The cured FI-UAR films exhibited enhanced glass transition temperature, thermal stability, transmittance, and yellowness. Also, the adhesion and haze of cured films were improved as the methylene chain length of the FI-UA oligomers increased.